Improving Yield and Quality of ‘Balady’ Mandarin Trees by Using Shading Techniques and Reflective Materials in Response to Climate Change Under Flood Irrigation Conditions - Hesham M. A. El-Zawily; Mohammed M. S. Abo El-Enin; Hayam M. Elmenofy; Islam F. Hassan; Ioanna Manolikaki; Georgios Koubouris; Shamel M. Alam-Eldein (Agronomy)
Considering climate change predictions, it is logical to anticipate detrimental effects on the mandarin tree, an essential citrus crop. Therefore, scientists should promptly focus on developing methods to enhance its resistance to climatic stress effects such as sunscald. This study assesses the strategies employed in ‘Balady’ mandarin trees when covered by shading nets of varying colors and percentages (white 50%, green 50% or 63%, black 50% or 63%), as well as the application of reflective materials (kaolin at 4% and CaCO3 at 3%) on the micro-climate of orchards, leaf, and fruit surface temperatures, fruit sunburn%, productivity, and fruit quality. The results indicated that shade nets effectively reduced temperature and enhanced humidity, especially during the period from June to September, when compared to open-field treatments. Black shade nets, particularly those with a shading level of 63%, demonstrated the most notable decrease in canopy temperature and an elevation in humidity, surpassing the performance of green and white shade nets. The present study found that shade nets and reflecting materials like kaolin and calcium carbonate significantly reduced fruit sunburn. Trees without shade had a sunburn rate of 8.74%, while those with shade treatments suffered no sunburn. Kaolin foliar spray at a concentration of 4% and calcium carbonate at a concentration of 3% reduced sunburn incidence to 3.64% and 7.32%, respectively. These treatments also reduced the intensity of sunburn. All treatments increased fruit yield % compared to the control and yield efficiency (kg/m2), especially the trees covered with white shade net of a 50% shading rate provided the highest values (43.70 and 40.17%) and (5.24 and 5.47 kg/m2) compared to other treatments in both seasons, respectively. Trees covered with a white shade net of a 50% shading rate, followed by a green shade net of 50% and a 63% shading rate, as well as a black shade net of 50% and a 63% shading rate, tended to improve the physical and chemical fruit properties. Therefore, it could be recommended that trees be covered with a white shade net of a 50% shading rate or a green shade net of a 50 and 63% shading rate in summer months due to its beneficial impact on mitigating fruit sunburn damage and enhancing the productivity and quality of ‘‘Balady’’ mandarin trees. Hence, shade nets can be a beneficial technology to protect citrus fruits from sunburn without affecting fruit quality in commercial citrus farms.